Characterisation and modeling of complex geometries using TexGen - Brown, Louise P.; Endruweit, Andreas; Long, Andrew C.; Jones, I. Arthur (2018)
TexGen is open source software developed at the University of Nottingham for the geometric 3D modelling of textiles and textile composites. It has a large number of users worldwide and underpins a significant number of research publications.